An easy-to-use liquid chromatography assay for the analysis of lamotrigine in rat plasma and brain samples using microextraction by packed sorbent:Application to a pharmacokinetic study - Ventura, Sandra (2016)
A simple and rapid high-performance liquid chromatography method with diode-array detection (HPLC-DAD) using microextraction by packed sorbent (MEPS) during the sample preparation step was developed and validated to quantify lamotrigine (LTG) in rat plasma and brain samples. MEPS variables such as pH, number of draw-eject cycles, and washing and desorption conditions were optimized. The chromatographic resolution of LTG and chloramphenicol, used as internal standard (IS), was accomplished in less than 5min on a C18 column, at 35°C, using an isocratic elution with acetonitrile (13%), methanol (13%) and water-triethylamine (99.7:0.3, v/v; pH 6.0) pumped at a flow rate of 1mL/min. Detection was performed at 215nm. Calibration curves were linear over the range of 0.1-20μg/mL (r2≥0.9947) for LTG in both rat plasma and brain homogenate samples. The intra and interday imprecision did not exceed 8.6% and the intra and interday inaccuracy ranged from -8.1 to 13.5%. LTG was extracted from rat plasma and brain homogenate samples with an average absolute recovery ranging from 68.0 to 86.7%, and its stability was demonstrated in the assayed conditions. No interferences were observed at the retention times of the analyte (LTG) and IS. To the best of our knowledge, this is the first bioanalytical assay that uses MEPS procedure for the determination of LTG not only in rat plasma but also in tissue (brain) samples. This novel method was successfully applied to a preliminary pharmacokinetic study in rats and it seems to be a cost-effective tool to support non-clinical pharmacokinetic-based studies involving LTG treatment.